Penerapan Metode ODOA (One Day One Ayat) dalam Meningkatkan Kemampuan Siswa Membaca Al Quran di Kelas IV SD Negeri 054905 Paya Redas - Zakiah Zakiah (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
The ability to read the Quran is a crucial aspect of Islamic education, particularly in Indonesia, where many students face challenges in recognizing Arabic letters and applying tajwid rules. This study aims to evaluate the implementation of the One Day One Ayat (ODOA) method in improving Quran reading skills among fourth-grade students at SD Negeri 054905 Paya Redas. Employing a qualitative case study approach, data were collected through direct observations, in-depth interviews with teachers, students, and parents, and analysis of students' learning outcomes. The findings indicate a significant improvement in students' reading abilities, with average test scores rising from 65 to 85 after several weeks of applying the ODOA method. Additionally, over 80% of students demonstrated a better understanding of the meaning of the verses studied. The study concludes that the ODOA method effectively enhances Quran reading skills and fosters a positive attitude toward religious learning, highlighting the importance of structured planning, implementation, and evaluation in educational practices.